Habitudes migratoires des elephants et interactions homme-elephant dans la region de Waza-Logone (Nord-Cameroun) - Tchamba, Martin (Pachyderm, 1998)
Three subpopulations exist in the Waza NP region: a sedentary group with a range of about 785 sq kms; a group which during the dry season migrates towards Kalamaloue NP 80 km north of Waza, and returns to Waza NP early in the rainy season; and, a group which migrates southwards into the Kaele region at the beginning of the rainy season, and returns to Waza early in the dry season. The range of the latter two groups are about 3,066 and 1,577 - 2,604 sq kms respectively. The 1991 estimated elephant population in the area was 1,100 (perhaps up to 1,400). Crop raiding elephants in southern Waza during the rainy season have increased from 50 in 1991 to 330 in 1997. Official estimates of the annual crop damage of 200 ha at US382,000 is an overestimate in the order of 46%. However, the US51,000 revenue generated from elephant related tourism cannot compensate for damage incurred. Loss of human life due to elephants is rare, and elephant mortality caused by humans is negligible. Conflict reduction measures: fencing, translocation of problem animals or financial compensation, should include legislative reforms and assistance to reinforce local wildlife management capacity.